The effect of listening to holy Qur’an recitation on labor pain in the first stage of labor - Ana Mariza; Christika Lucia Anggraini (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2020)
Background: Pain during labor is a physiological condition experienced by almost all maternity mothers. The hardest time, and most mothers begin to feel pain or pain at the time of delivery is when I active phase.Purpose: To known the effect of listening to holy Qur'an recitation on labor pain in the first stage of laborMethods: A quantitative by experimental quasi research design, with one group pretest - posttest design approach. The population of all who are on the first stage of labor. By purpose sampling technique got of 15 respondents. Data analysis with t-test.Results: Finding of the average pain before listening to holy Qur'an recitation of 5.93, and after intervention of 3.93. Knowing there is Effect of listening to holy Qur'an recitation on labor pain in the first stage of labor. T test results obtained p value 0,000 <α (0.05). It is recommended for hospital management, especially midwives, to provide therapy to listening to holy Qur'an recitation as alternative to reduce of labor pain in the first stage of labor